Management of Murabahah and Musyarakah Financing Products at BMT Saudara Magelang as an Islamic Non-Bank Institutions - Siti Masruroh; Fuad Yanuar Ahmad; Yeny Fitriyani (Mutanaqishah: Journal of Islamic Banking, 2024)
This study focuses on the management of murabahah and musyarakah financing products at BMT Saudara, a non-bank Islamic financial institution. The objective is to understand and improve product management at BMT Saudara. The research methods include interviews, observations, and documentation. The findings show that BMT Saudara successfully implements murabahah and musyarakah financing schemes according to Sharia principles. These financing products reflect a deep understanding of Sharia principles. The study provides insights into best practices in managing Islamic financing products at non-bank financial institutions, particularly at BMT Saudara. These findings are expected to support further improvements and developments to enhance the effectiveness of murabahah and musyarakah financing product management in the Islamic finance environment. The implications of these findings include improved product management practices that can contribute to the growth and stability of non-bank Islamic financial institutions like BMT Saudara.